Discrimination of chiral compounds using NMR spectroscopy - Wenzel, Thomas J. (Wiley-Interscience, 2007)
This guide describes the various systems and their overall utility, but goes further to show the full scope of the field as a way of guiding investigations into the optimal chiral reagents for use in NMR spectroscopy. It's a practical reference for organic chemists in the pharmaceutical industry, academia, and other areas, NMR spectroscopists, and researchers involved in the isolation and structure determination of natural products